BULLING IN THE LABOR COLLECTIVE AS A SOCIAL PROBLEM OF SOCIETY (American Journal of Research in Humanities and Social Sciences, 2025)
In this article, we have examined and analyzed one of the common types of bullying bullying within the labor collective. Its victims are usually competent, responsible, and balanced employees who are fully dedicated to their professional activities. The main goal of aggressors in such situations is to displace a person from the collective and force them to leave.